Small Airway Dysfunction in Cough Variant Asthma: Prevalence, Clinical, and Pathophysiological Features - Yi, Fang; Jiang, Ziyu; Li, Hu; Guo, Chunxing; Lu, Hankun; Luo, Wei; Chen, Qiaoli; Lai, Kefang (Frontiers in Physiology, 2022)
Introduction: Small airway dysfunction (SAD) commonly presents in patients with classic asthma, which is associated with airway inflammation, disease severity, and asthma control. However, the prevalence of SAD, its relationship with cough severity and airway inflammation, and its development after antiasthmatic treatment in patients with cough variant asthma (CVA) need to be clarified. This study aimed to investigate the prevalence of SAD and its relationship with clinical and pathophysiological characteristics in patients with CVA and the change in small airway function after antiasthmatic treatment. Methods: We retrospectively analyzed 120 corticosteroid-naïve patients with CVA who had finished a standard questionnaire and relevant tests in a specialist cough clinic, such as cough visual analog scale (VAS), differential cells in induced sputum, fractional exhaled nitric oxide (FeNO) measurement, spirometry, and airway hyper-responsiveness. Information of 1-year follow-up was recorded in a part of patients who received complete cough relief after 2 months of treatment. SAD was defined as any two parameters of maximal mid-expiratory flow (MMEF)% pred, forced expiratory flow at 50% of forced vital capacity (FEF50%) pred, and forced expiratory flow at 75% of forced vital capacity (FEF75%) pred measuring <65%. Results: SAD occurred in 73 (60.8%) patients with CVA before treatment. The patients with SAD showed a significantly longer cough duration (24.0 vs. 6.0, p = 0.031), a higher proportion of women (78.1 vs. 59.6%, p = 0.029), older mean age (41.9 vs. 35.4, p = 0.005), and significantly lower forced expiratory volume in 1 s (FEV1%) pred, FEV1/FVC, MMEF% pred, FEF50% pred, FEF75% pred, PEF% pred, and PD20 (all p < 0.01) as compared with patients without SAD. There were no significant differences in cough VAS, sputum eosinophils count, FeNO, and TIgE level between patients with SAD and those without SAD. Among 105 patients who completed 2 months of antiasthmatic treatment and repeatedly experienced spirometry measurement, 57 (54.3%) patients still had SAD, despite a significant improvement in cough VAS, sputum eosinophils, FeNO, FEF50% pred, and PEF% pred (all p < 0.01). As compared with patients without SAD, patients with SAD showed no significant differences in the relapse rate (50.0 vs. 41.9%, p = 0.483) and wheeze development rate (10.4 vs. 0%, p = 0.063) during the follow-up. Conclusions: Small airway dysfunction occurred in over half of patients with CVA and persisted after short-term antiasthmatic treatment, which showed distinctive clinical and pathophysiological features.